Explaining the Structural Model of Health Anxiety Based on Metacognitive Beliefs with the Mediating Role of Anxiety Sensitivity in Individuals with Obsessive–Compulsive Symptoms - NikArdestani, Seyyed Mohammad Hassan; Nikyar, Hamidreza; Talebi, Gholamreza (International Journal of Education and Cognitive Sciences, 2025)
Purpose: The present study aimed to clarify a structural equation model of health anxiety based on metacognitive beliefs, with anxiety sensitivity serving as a mediator among individuals with obsessive–compulsive symptoms.Methods and Materials: This descriptive–correlational research utilized structural equation modeling. The statistical population consisted of all individuals exhibiting obsessive–compulsive symptoms who attended counseling centers, psychological clinics, and psychiatric clinics in Isfahan during 2024–2025. A convenience sample of 480 participants was selected. The research instruments included the Short Health Anxiety Inventory (SHAI) developed by Salkovskis and Warwick, the Metacognitions Questionnaire-30 (MCQ-30) by Wells and Cartwright-Hatton, and the Anxiety Sensitivity Index (ASI) by Floyd et al. Data analysis was performed using SPSS and AMOS software, and structural equation modeling with bootstrapping was applied to test the hypotheses.Findings: The findings revealed that all direct paths among the study variables were statistically significant at p < 0.05. Anxiety sensitivity significantly mediated the relationship between metacognitive beliefs and health anxiety. The bootstrap analysis indicated that the indirect effect of metacognitive beliefs on health anxiety was 0.141, which was significant at the 0.05 level.Conclusion: The results demonstrated that dysfunctional metacognitive beliefs contribute to the development of health anxiety by heightening anxiety sensitivity. Consequently, modifying maladaptive metacognitive beliefs and implementing interventions aimed at reducing anxiety sensitivity—such as interoceptive exposure and symptom reappraisal—can play a vital role in managing and alleviating health anxiety among individuals with obsessive–compulsive symptoms.